Pelatihan Seni Kaligrafi Untuk Generasi Emas Bagi Siswa Di Sekolah Dasar 050612 Desa Suka Jadi - Muhammad Ilham; Efi Cahayani; Muhammad Rizki Zakaria (peduli riset dan pengabdian masyarakat, 2025)
This calligraphy training program conducted at SDN 050612 Suka Jadi Village aims to introduce calligraphy as an art form to elementary school students, enhancing their artistic skills, fostering an appreciation for cultural arts, and providing insights into the significance of calligraphy in Islamic contexts. The program was conducted in two sessions: the first for introducing the theory of calligraphy, and the second for hands-on practice in writing Arabic letters. Using methods of lectures, demonstrations, and direct practice, the training successfully showed positive results, where students exhibited improvements in their calligraphy skills. Despite some challenges such as time constraints and limited resources, this training program successfully engaged students and provided long-term benefits, particularly in their artistic development.